Ação do tipo-antidepressiva do sulfeto de [(4-terc-butilciclohexilideno) metil] (4-metoxiestiril) em camundongos: envolvimento dos sistemas serotoninérgico e nitrérgico - Oliveira, Renata Leivas de (2019)
Depression is considered one of the most prevalent psychiatric disorders, causing a major negative impact on the quality of life of their patients. The search for new antidepressant agents has intensified, given that current treatments show some limitations regarding their therapeutic effect. Organocalcogen compounds are considered an important class of molecules with various therapeutic effects in animal models, among them the stands out are ((4-tert-butylcyclohexylidene) methyl) (4- methoxystyryl) sulfide (BMMS), in which in previous studies demonstrated several pharmacological activities. In view of this, the present study investigated a possible antidepressant-like effect of ((4-tert-butylcyclohexylidene) methyl) (4-methoxystyryl) sulfide (BMMS) using the forced swimming test (FST) and the tail suspension test (TST) in male Swiss mice. The contribution of serotoninergic, glutamatergic and nitrergic systems in the antidepressant-like effect of BMMS was evaluated. We also examined the involvement of monoamine oxidase (MAO)-A, MAO-B and Na+ /K+ - ATPase activities in prefrontal cortex of mice. BMMS (0.1-10 mg/kg, intragastrically (i.g.)) and fluoxetine (32 mg/kg, i.g.) decreased the immobility time in the FST and TST. The anti-immobility effect of BMMS (10 mg/kg, i.g.) in the TST was completely prevented by the pretreatment with WAY100635 (0.1 mg/kg, subcutaneously (s.c.), a 5-HT1A receptor antagonist), ketanserin (5 mg/kg, intraperitoneal (i.p.), a 5-HT2A/2C receptor antagonist), and partially blocked by ondansetron (1 mg/kg, i.p., a 5-HT3 receptor antagonist). The anti-immobility effect of BMMS was not avoided by pretreatment with MK-801 (0.01 mg/kg, s.c. a N-methyl D-Aspartate (NMDA) receptor non-competitive antagonist) in the TST. Pretreatment with L-arginine (500 mg/kg, i.p., a nitric oxide precursor) reversed partially the reduction in the immobility time elicited by BMMS in TST. BMMS altered Na+ /K+ -ATPase and MAO-A activities in prefrontal cortex of mice, but was not able to change the MAO-B activity. In conclusion, BMMS exerted an antidepressant-like effect in mice and serotonergic and nitrergic systems are involved in the antidepressant-like action of compound. In addition, selective inhibition in MAO-A activity and the increase in Na+ /K+ -ATPase activity are involved in the antidepressant-like effect of BMMS. Our results inferred that BMMS is a multitarget compound, but further studies are needed to elucidate the other mechanisms of action and the contribution of other neurotransmission systems to antidepressant-like action of BMMS.